A Quantum Mechanical Aspect of Cold Fusion - Makar, Ayan Kumar (The Physical Society of Indonesia, 2025)
The current study presents a quantum mechanical model for low-energy nuclear fusion in a deuterium-loaded palladium lattice, based on the modification of the Coulomb interaction between deuterons due to environmental screening effects. In this framework, deuterons are treated as charged bosons embedded in a conductive metallic lattice, where their mutual repulsion is significantly reduced by the surrounding conduction electron cloud and collective plasma behavior. The interaction is modeled using a screened Coulomb (Yukawa-type) potential, and the probability of nuclear fusion is evaluated through a semiclassical WKB approximation. Numerical estimates incorporating realistic deuteron densities and lattice parameters yield tunneling probabilities and fusion rates consistent with non-negligible low-temperature fusion activity. The results obtained indicate that under high deuterium loading conditions, the environment-induced screening of the Coulomb barrier can enhance tunneling sufficiently to allow measurable fusion rates, offering a plausible mechanism for solid-state fusion without the need for extreme thermal conditions as one of the aspects of cold fusion.